Reimagining Thai, Jazz, and Classical Musical Identities in “Phosop”: The Music of Awakening the Spirit - Chaichana, Tanarat (Institut Seni Indonesia Yogyakarta, 2025)
Historically, Eurocentrism has profoundly influenced the development, perception, and evaluation of cross-cultural music, shaping composers’ perspectives and reinforcing biases related to notions of identity and authenticity. This dynamic also exposes underlying power imbalances between Western and non-Western cultures, especially in musical collaborations. In response, this paper advocates for a reconciliatory approach that addresses these issues and strengthens the concept of decolonization in music composition. This study examines an original composition for orchestra, jazz quartet, and khaen, titled “Phosop,” identifying how it embodies the principles of cultural recognition, the dismantling of hierarchical structures, and the promotion of collective participation through a deliberate process that integrates jazz, classical, and Isan Nuea music. The collaborative interaction among these distinct styles exemplifies a shared musical dialogue that balances individual expression with collective creation, honoring diverse cultural heritages. Consequently, this work advocates for a participatory and dialogic model of music-making that fosters inclusivity, encouraging composers to critically engage with the histories and contributions of various musical traditions by adopting inclusive practices. These practices aim to elevate and honor cultural narratives through artistic work, thereby challenging Eurocentrism in global or cross-cultural music composition. Such efforts contribute to the cultivation of a more equitable and dynamic global musical landscape, fostering cross-cultural understanding and amplifying diverse voices.